2013
DOI: 10.1007/s00330-013-2844-8
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of multidetector-row CT for restaging after neoadjuvant treatment in patients with oesophageal cancer

Abstract: OBJECTIVES: To assess the diagnostic accuracy of 64-multidetector CT (MDCT) for restaging of patients with oesophageal cancer undergoing neoadjuvant therapy. METHODS: Results of pathological staging were correlated with those from 64-MDCT before and after neoadjuvant treatment in 35 patients using the American Joint Committee on Cancer/TNM classification (7th edition). CT response was determined using the Response Evaluation Criteria in Solid Tumours (RECIST) method, modified for one-dimensional tumour diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
(76 reference statements)
3
16
0
Order By: Relevance
“…To implement non‐surgical treatment for advanced oesophageal cancer it is critical to accurately identify pCR. CT and fluorodeoxyglucose (FDG) PET/CT are both inaccurate in discriminating residual disease from pCR owing to the presence of wall thickening and/or radiation oesophagitis. The same is true for endoscopic ultrasonography (EUS), which has an accuracy of only 36 per cent for ypT determination.…”
Section: Introductionmentioning
confidence: 99%
“…To implement non‐surgical treatment for advanced oesophageal cancer it is critical to accurately identify pCR. CT and fluorodeoxyglucose (FDG) PET/CT are both inaccurate in discriminating residual disease from pCR owing to the presence of wall thickening and/or radiation oesophagitis. The same is true for endoscopic ultrasonography (EUS), which has an accuracy of only 36 per cent for ypT determination.…”
Section: Introductionmentioning
confidence: 99%
“…The few published studies evaluating the predictive value of CT response assessment after neoadjuvant therapy in esophageal cancer have been inconclusive. Although changes in CT tumor volume showed greater correlation with pathological response than changes in tumor diameter and were associated with lower interobserver variability, it is only a modest predictor of pathological response at best (Table ) . The cut‐offs used for changes in tumor volume to differentiate responders from non‐responders ranged from 10% to 20% .…”
Section: Ctmentioning
confidence: 99%
“…The few studies that evaluated early CT response assessment showed limited utility in the neoadjuvant CRT and chemotherapy setting with poor sensitivity and negative predictive value (NPV) (Table ). The ability of late CT assessment in predicting pathological response and TNM stage is poor (Table ) . There is suggestion that CT may perform better in those treated with neoadjuvant chemotherapy compared with CRT, although this is based on very few studies with no direct comparison of its predictive ability between the two treatment modalities in any of these studies (Table ) …”
Section: Ctmentioning
confidence: 99%
See 2 more Smart Citations